Pengaruh Kepuasan Kerja Terhadap Kinerja Karyawan Di Daima Hotel Padang - Viola Witya Santika; Yuliana Yuliana (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2018)
Abstract. Thenpurposerof this studyswas to determine the effecttof job satisfaction on employee performance at Daima Hotel Padang. This type of research is quantitative with causal assumtion. The sampling technique used is saturated sampling with 54 people as sample. Data collection techniques are carried out by distributing questionnaries using aslikert scaledthat has been tested for validitysand reliability. Thenresults of the studyefoundsthat variable jobysatisfaction hasnan influenceroneemployee performancesvariables by 20,6% and 79,4% influenced by other factors. Keywords: Job Satisfaction, Employee Performance, Hotel